THEORETICAL ASPECTS OF THE PROCESS OF CENTRIFUGAL GRAIN UNLOADING IN THE ELEVATOR OF COMBINE HARVESTERS - Бурлака, О. А.; Яхін, С. В. (Scientific Progress & Innovations, 2017)
The disadvantages of the lifting elevators of КZS-9-1 combine harvesters are imperfections of centrifugal unloading, as a result of which there is increase of energy for transportation, the degree of crushed and damaged grain increases, wear of the elevator's working members is accelerated. Based on theoretical studies, taking into account the oscillations of the chain transmission, it is offered to increase the unloading sectors to the condition that the grain transit time along the scraper and the time for the scraper of the discharge sector to coincide.